2008
DOI: 10.1182/blood-2007-09-111708
|View full text |Cite
|
Sign up to set email alerts
|

Total body irradiation, etoposide, cyclophosphamide, and autologous peripheral blood stem-cell transplantation followed by randomization to therapy with interleukin-2 versus observation for patients with non-Hodgkin lymphoma: results of a phase 3 randomized trial by the Southwest Oncology Group (SWOG 9438)

Abstract: To determine the effect of posttransplantation immunotherapy with IL-2 on the progression-free survival (PFS) and overall survival (OS) of patients with nonHodgkin lymphoma (NHL) after autologous stem-cell transplantation (PBSCT), patients with previously treated NHL were treated with cyclophosphamide, etoposide, total body irradiation (TBI), and PBSCT. Twenty-eight to 80 days after PBSCT, patients were randomized to IL-2 versus observation. Three hundred seventy-six eligible patients were registered (with 4-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Interleukin-2 (IL-2) maintenance has been given in a variety of dosing schedules to up-regulate T cell immunity, but Phase III studies showed no effect on outcome after auto-HCT for NHL, AML or ALL. 58 Another approach was the induction of autologous GvHD using cyclosporine A (CSA) with interferon-γ (IFNγ) and IL-2. However, a randomized trial showed no benefit with this approach in patients with poor risk lymphoma.…”
Section: Preventing Relapse After Autologous Hematopoietic Cell Transmentioning
confidence: 99%
“…Interleukin-2 (IL-2) maintenance has been given in a variety of dosing schedules to up-regulate T cell immunity, but Phase III studies showed no effect on outcome after auto-HCT for NHL, AML or ALL. 58 Another approach was the induction of autologous GvHD using cyclosporine A (CSA) with interferon-γ (IFNγ) and IL-2. However, a randomized trial showed no benefit with this approach in patients with poor risk lymphoma.…”
Section: Preventing Relapse After Autologous Hematopoietic Cell Transmentioning
confidence: 99%
“…The additional rationale for bringing IL-2 therapy into the posttransplant setting is its potential contribution to immunologic recovery and even the stimulation of a new, lesstolerized immune response to tumor antigens, analogous to the melanoma studies detailed earlier. Despite promising early pilot data [34][35][36][37], the randomized studies to evaluate the contribution of IL-2 following autologous transplant in leukemia and lymphoma failed to demonstrate a benefit [38,39]. Its potential role as an adjunct to post-transplant manipulations such as donor lymphocyte infusions following allogeneic transplant remains under evaluation ( Table 2).…”
Section: Il-2-based Therapy Of Hematologic Malignanciesmentioning
confidence: 98%
“…A variety of immune-modulating agents have been used in small series and case reports, including cyclosporine, interferons, and interleukins (see comprehensive review by Kline et al [ 56 ]). Most recently, the Southwest Oncology Group published long-term data on a phase 3 randomized trial of ASCT for relapsed lymphoma patients with or without adjuvant interleukin-2 (IL-2) [ 57 ]. The researchers did not fi nd improvements in PFS or OS, and concluded that the dose and schedule of IL-2 administered did not benefi t patients.…”
Section: Posttransplant Therapies To Reduce Minimal Residual Diseasementioning
confidence: 98%